2005
DOI: 10.1002/adma.200400628
|View full text |Cite
|
Sign up to set email alerts
|

Towards Protein Field‐Effect Transistors: Report and Model of a Prototype

Abstract: Since the early 1970s, the electronics industry has been essentially identified with metal-oxide semiconductor (MOS) large-scale integrated circuits. During the past decades, remarkable advances have been accomplished by the downsizing of components (such as MOS field-effect transistors), and the number of transistors on a chip has continuously increased in accordance with Moore's law thanks to constant improvements in lithographic resolution (the top±down approach). However, this approach is unlikely to be su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
77
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 33 publications
1
77
2
1
Order By: Relevance
“…There are many studies that focus on nanodevices with the integration of nanogap electrodes and organic molecules (small molecules, [153] oligomers, [154,155] polymers, [156] fullerenes, [8,157] and biomolecules, [158][159][160][161] etc.) or other nanometer-sized components (CNTs, [162] nanocrystals, [84,163] etc.)…”
Section: Applicationsmentioning
confidence: 99%
“…There are many studies that focus on nanodevices with the integration of nanogap electrodes and organic molecules (small molecules, [153] oligomers, [154,155] polymers, [156] fullerenes, [8,157] and biomolecules, [158][159][160][161] etc.) or other nanometer-sized components (CNTs, [162] nanocrystals, [84,163] etc.)…”
Section: Applicationsmentioning
confidence: 99%
“…Studying electron transport (ETp) via solid-state molecular junctions represents an approach, bridging the study of basic ET-related phenomena and electronic devices, where measuring ET rates as a function of an electrochemical driving force is replaced by measuring current across molecular junctions as a function of an applied electrical voltage (20). Combining the concepts and methods of molecular electronics such as currentvoltage (I-V) line-shape analysis (21,22), temperature-dependent measurements (23,24), and electronic spectroscopy techniques (25)(26)(27) may yield new insights into the mechanism of ETp across the peptide matrix of proteins (28)(29)(30) and pave the road to peptide-and protein-based electronic devices for switching, rectification, and memory (18,31).…”
mentioning
confidence: 99%
“…It was reported by direct charge transport experiments that double-stranded DNA (dsDNA) could exhibit fascinating physical phenomena, such as the proximity-induced superconductivity [21], the negative differential resistance [22], and the piezoelectric effect [23]. Additionally, it was shown that both dsDNA and α-helical protein can behave as electric field-effect transistors [24][25][26][27] and as efficient spin filters [28][29][30][31][32][33][34][35]. …”
mentioning
confidence: 99%